X-ray crystal structures of nickel and cobalt alpha-hydroxyoxime-carboxylic acid synergist complexes - Barnard, K.; McIldowie, Matthew; Nealon, Gareth; Ogden, Mark; Skelton, B. (Gecamin Ltda, 2011)
A reagent that has regularly found use in synergistic systems is LIX63, the active component of which is 5,8-diethyl-7-hydroxydodecan-6-oxime (LH). The use of LIX63 in conjunction with a carboxylic acid (RH) to synergistically extract metal ions and form mixed-ligand complexes was first reported in 1969. Given that both ligands are capable of deprotonation, it has long been of interest to ascertain which of them acts as the anion and which acts as the neutral (synergist)species. However, information on the species formed in this system has traditionally been limited to equilibrium studies and UV-visible analysis. In the present work, the X-ray crystal structures of ‘model’ cobalt and nickel synergist complexes, synthesised using a short chained (C8) analogue ofLIX63 hydroxyoxime and isobutyric acid, are presented and discussed. The complexes have been found to have the same structure wherein the two acid groups are present in the anionic form and are located cis to one another. The two chelated alpha-hydroxyoxime ligands are uncharged with the oxime nitrogen atoms located trans to one another. Intra-molecular hydrogen bonding between each carboxylate carbonyl group and a cis-adjacent oxime hydroxyl group is evident. Unlike the phenolic-based hydroxyoxime-metal complexes and the previously proposed structure, no intra-molecular hydrogen bonding between the hydroxyoxime ligands is apparent. These structures provide the first definitive structural elucidation of the types complexes able to be formed via synergistic solvent extraction utilising LIX63 and carboxylic acids.